The Modernization of English Learning Techniques in Semarang Regency Islamic Junior High Education Boarding School: A SWOT Analysis - Suesthi Maharani (Journal of English Language Learning, 2024)
English in Indonesia was still considering an exclusive international language, so discussing English with advantages in its learning techniques became something taken into modern and contemporary with Islamic educational institutions such as Islamic Junior High Education or Islamic boarding school. Because its position was so important, learning English became very urgent to be reviewed by its strengths, weaknesses, opportunities, and challenges to ease effective and efficient learning to be more readily accepted by students. This study aimed to explain the application of English learning techniques modernization in Semarang regency Islamic junior high education boarding school and analyze the strengths, weaknesses, opportunities, and challenges in applying English learning techniques modernization. This study was intended to describe the situation as it was about a variable or circumstances about the Modernization of English Learning Techniques in Semarang Regency Islamic Junior High Education Boarding School by analyzing the strength, weakness, opportunity, and threats. The data were collected using triangulation techniques where researchers used different data collection techniques to get data from the same source, namely participatory observation, in-depth interviews, and documentation. The qualitative data analysis was used based on the instruments such as observation sheets, discussions, and documentation.